STRATEGI PENGEMBANGAN USAHA SAMBAL IKAN ROA PADA INDUSTRI âCITARASAKUâ KELURAHAN TINGGEDE KECAMATAN MARAWOLA KABUPATEN SIGI - Haryanto, Malan; Rauf, Rustam Abd (AGROTEKBIS, 2017)
This study aims to determine the business development strategies of fish sambal roa right Â Â to apply to Industry